Estudo da interação DNA-ciclodextrina com a técnica de pinçamento óptico com aplicação em terapia gênica - Livia Siman Gomes (2009)
In one of the methods of gene therapy, DNA of normal cells are encapsulated inside liposomes (lipids vesicles) which are transferred by endocytosis into the unhealthy cells. However, the amount of pure DNA that may be absorbed by liposomes of typical dimensions of tenths of microns is small. One solution to this problem is to promote the condensation of the DNA by drugs in complexes DNA- drugs where the DNA keeps its functions of conserving and transferring genetic information. The aim of the research described here was to test the formation of complexes of DNA with the drug cyclodextrin (CD). In our experiments single DNA molecules were stretched (in the limit of entropic forces) by optical tweezers and their length measured for several DNA- CD concentrations. The corresponding forces x extension curves were analyzed according to the Worm-Like Chain (WLC) model of Marko and Siggia to obtain the persistence lengths which is related to the DNA molecule rigidity. An unusual behavior for the persistence length as a function of CD concentration was obtained. As a practical outcome of this work is the prediction of the best CD concentration to be used in gene therapy. This work was developed in collaboration with Dr. Mônica C. de Oliveira from the School of Pharmacy at UFMG.